Accumulation and partitioning of biomass and macronutrients of bush snap bean genotypes in semi-hydroponic system (Colloquium Agrariae. ISSN: 1809-8215, 2020)
For a better management of fertigation in protected cultivation of vegetables such as snap beans, it is important to know the nutritional requirements of the plants. Thus, we aimed to characterize the biomass and nutrients accumulation of bush snap beans genotypes. For that, an experiment was carried out in greenhouse, where the genotypes UEL-1 and Alessa were grown in plastic pots with coarse sand as substrate and fertigation by micro sprinklers. Each ten days, plants were sampled and measured the dry matter and the concentrations of elements such as nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S), adjusting their accumulation over time by the gaussian model. The fresh pods yield (kg m-2) was also evaluated. The accumulation of biomass and macronutrients are intensified from 20 days after emergence (DAE), reaching maximum values near 50 DAE. The genotype Alessa presented a higher overall accumulation, while UEL-1 was more productive regarding fresh pods, characterizing such genotype as more efficient for using the macronutrients. For both genotypes, N had the highest accumulation, followed by K, Ca, P, S and Mg.